Current Issues in Ciphertext Policy-Attribute Based Scheme for Cloud Computing: A Survey - Muhammad, Norhidayah; Mohamad Zain, Jasni; Mohamad, Mumtazimah (International Journal of Engineering and Technology, 2018)
The use of cloud computing has increased exponentially in data resources storage over the past few years. Cloud storage reduces the overall costs of server maintenance, whereby companies only pay for the resources they actually use in the cloud storage. Despite this, security concerns in cloud computing must be a top priority. One of the common encryption methods in cloud security is Attribute Based Encryption (ABE). ABE contains two types, namely, Ciphertext Policy-Attribute Based Encryption (CP-ABE) and Key Policy- Attribute based Encryption (KP-ABE). CP-ABE is better than KP-ABE, especially in reduplication issues and fine-grained access. However, issues in CP_ABE need further improvement. Improvement for the CP-ABE scheme has been growing rapidly since 2010 to date, and five main issues need improvement. This paper reviews the proposed CP-ABE schemes during the past three years.Â  These schemes focus on solving the five issues identified inherent in the CP-ABE scheme.Â